The effectiveness of automatic identification system use on ship surveillance in navigation district type a class 1 Makassar - Rachman, Subehana; Asri, Haerani; Kendek, Meti; Rahmah, Annisa; Sulistiana, Oktavera (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the effectiveness of the Automatic Identification System (AIS) in supporting ship surveillance activities within the Navigation District Type A Class 1 Makassar. The primary objective is to assess how AIS contributes to enhancing maritime safety, improving vessel monitoring accuracy, and supporting decision-making processes for navigation authorities. A qualitative-descriptive methodology was employed, combining field observations, document analysis, and structured interviews with relevant stakeholders, including district officers and vessel operators. Data collected was analyzed to determine the system’s strengths, limitations, and overall impact on operational performance. The results show that AIS significantly enhances ship surveillance capabilities, particularly in high-density maritime routes such as the Makassar Strait. The system enables real-time tracking of vessel movements, facilitates the identification of illegal or unregistered ships, and improves communication during emergencies. Nevertheless, the research identified several challenges, including limited AIS coverage in remote areas, outdated equipment on smaller vessels, and the need for continuous technical training for operators. The study concludes that AIS is a vital tool in ensuring maritime safety and efficiency in the Makassar region. Practical implications include the need for infrastructure upgrades, policy improvements, and capacity building. These findings are expected to support future developments in maritime surveillance systems across Indonesia’s navigation districts.